1995
DOI: 10.1007/bf00020393
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Chlamydomonas reinhardtii gene encoding a protein of the DNA photolyase/blue light photoreceptor family

Abstract: The organization and nucleotide sequence of a gene from Chlamydomonas reinhardtii encoding a member of the DNA photolyase/blue light photoreceptor protein family is reported. A region of over 7 kb encompassing the gene was sequenced. Northern analysis detected a single 4.2 kb mRNA. The gene consists of eight exons and seven introns, and encodes a predicted protein of 867 amino acids. The first 500 amino acids exhibit significant homology with previously sequenced DNA photolyases, showing the closest relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 19 publications
0
58
0
Order By: Relevance
“…This view is consistent with the results that the addition of DCMU and the deletion of the PS little affected the low-light accumulation. Although phytochrome has not been reported in C. reinhardtii, a protein with retinal as chromophore (chlamyopsin; Deininger et al, 1995) and a homolog of cryptochrome (CPH1; Small et al, 1995) have been identified. Kindle (1987) proposed that the light-induced expression of a Lhc gene is controlled by a system with a blue-light receptor rather than by a phytochrome in C. reinhardtii, although the photoreceptor has not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
“…This view is consistent with the results that the addition of DCMU and the deletion of the PS little affected the low-light accumulation. Although phytochrome has not been reported in C. reinhardtii, a protein with retinal as chromophore (chlamyopsin; Deininger et al, 1995) and a homolog of cryptochrome (CPH1; Small et al, 1995) have been identified. Kindle (1987) proposed that the light-induced expression of a Lhc gene is controlled by a system with a blue-light receptor rather than by a phytochrome in C. reinhardtii, although the photoreceptor has not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
“…;Ahmad and Cashmore, 1993;Batschauer, 1993;Guo et al, 1998;Ninu et al, 1999), monocots (rice, barley, etc. ;Lin and Cashmore, 1996;Imaizumi et al, 2000;Perrotta et al, 2001), fern ( Adiantum capillus-veneris ;Kanegae and Wada, 1998;Imaizumi et al, 2000), moss ( Physcomitrella patens ;Imaizumi et al, 2001), and algae ( Chlamydomonas reinhardtii ; Small et al, 1995). Most plant species studied contain multiple cryptochromes.…”
Section: Cryptochromes Are Found Throughout the Plant Kingdommentioning
confidence: 99%
“…But CRY1 and CRY2 mRNA levels have been recently shown by a DNA microarray analysis to oscillate with a circadian rhythm of relatively low amplitudes (Harmer et al, 2000). Tomato CRY1 and CRY2, and Chlamydomonas CPH1 gene showed no obvious light regulation for their mRNA expression (Small et al, 1995;Perrotta et al, 2000). On the other hand, white mustard SaPHR gene expression is light induced, and both developmental regulation and light regulation of mRNA expression have been reported for some fern cryptochrome genes (Batschauer, 1993;Imaizumi et al, 2000).…”
Section: Light Regulation Of Cryptochrome Expressionmentioning
confidence: 99%
“…Mutations in CRY2 confer a late-flowering phenotype (74). A CRY gene has been isolated from the alga Chlamydomonas reinhardtii (75) and five CRY genes were found in the fern Adiantum capillus-veneris (76). However, there are no genetic data on the functions of CRYs in these organisms.…”
Section: Blue-light Photoreceptors/cryptochromesmentioning
confidence: 99%